Potato (Solanum tuberosum) aeroponics for quality seed production in north eastern Himalayan region of India - BAG, T K; SRIVASTAVA, A K; YADAV, S K; GURJAR, M S; DIENGDOH, L C; RAI, R; SINGH, SUKHWINDER (The Indian Journal of Agricultural Sciences, 2015)
The study was conducted at Central Potato Research Station, Shillong during 2013 and 2014 to evaluate the performance of three potato (Solanum tuberosum L.) varieties, viz. Kufri Megha, Kufri Himalini and Kufri Himsona in an aeroponics system installed under net cum polyhouse. All the varieties exhibited more than 90% survival with root initiation within 4-5 days of transplanting. Kufri Megha started tuber initiation within a month in both the years. Tuber initiation was late in Kufri Himalini in 2014 (60 days) as compared to 2013 (39 days). Kufri Himsona exhibited delayed tuber initiation at 69 to 75 days after transplanting in both the years. The first picking was done within 40 and 80 days after transplanting in Kufri Megha and Kufri Himsona, respectively, in both the years. First picking in Kufri Himalini was delayed by 15days in 2014 as compared to 50 days after transplanting in 2013 due to delayed tuber initiation. The crop duration of Kufri Megha was 110 and 134 days in 2013 and 2014, respectively, allowing for 8 to 9 pickings that yielded 108 to 118 gÂ ubers/plant (38 to 42 tubers/plant) with mean mini-tuber weight of 2.91 to 2.96 g. The number of pickings reduced significantly from 11 to 5 in Kufri Himalini and 7 to 4 in Kufri Himsona from 2013 to 2014. In Kufri Himalini, delay in tuber initiation and reduction in crop duration was observed in 2014. There was a significant reduction in per plant yield in both Kufri Himalini (162 g to 102 g) and Kufri Himsona (138 g to 39.25 g) accompanied by reduction in number of tubers/plant (38 to 27 tubers in Kufri Himalini and 29 to 11 tubers in Kufri Himsona). The mean mini-tuber weight also reduced from 4.32g to 3.87g in Kufri Himalini and 5.03g to 4.13g in Kufri Himsona.